FRAMEWORK FOR DESIGN OF SECURITY SYSTEMS FOR MONITORING EXAMINEES AND PROCTORS DURING EXTERNAL OFFLINE EXAMINATIONS IN NIGERIA - Adoga, Peter Ikpe (FUDMA JOURNAL OF SCIENCES, 2023)
This paper seeks to design a system for monitoring the compliance of external examination centers to set rules and regulations governing the conduct of an external offline examination. The system is designed to check impersonation of examinees, aiding and abetting by teachers and other proctors, importing and submitting answer scripts written outside the approved examination halls and finally monitoring the script submission process to prevent swapping of answer booklets after completion of the examination. The proposed system consist of biometric authentication system, automated attendance system, Closed-Circuit Television (CCTV) cameras for video recording, a script submission system (SSS), a drop box for temporal storage of scripts and human monitors to analyse the recorded videos at monitoring center of the examination board. The system is designed to work even in remote areas with unstable internet as is the case with most examination centers in rural areas in Nigeria. When implemented the system will help check illegal activities in miracle examination centers and reduce examination malpractices by both examinees and proctors drastically.